Music Education at School: Too Little and Too Late? Evidence From a Longitudinal Study on Music Training in Preadolescents - Carioti, Desiré; Danelli, Laura; Guasti, Maria T.; Gallucci, Marcello; Perugini, Marco; Steca, Patrizia; Stucchi, Natale Adolfo; Maffezzoli, Angelo; Majno, Maria; Berlingeri, Manuela; Paulesu, Eraldo (Frontiers in Psychology, 2019)
It is widely believed that intensive music training can boost cognitive and visuo-motor skills. However, this evidence is primarily based on retrospective studies; this makes it difficult to determine whether a cognitive advantage is caused by the intensive music training, or it is instead a factor influencing the choice of starting a music curriculum. To address these issues in a highly ecological setting, we tested longitudinally 128 students of a Middle School in Milan, at the beginning of the first class and, one year later, at the beginning of the second class. 72 students belonged to a Music curriculum (30 with previous music experience and 42 without) and 56 belonged to a Standard curriculum (44 with prior music experience and 12 without). Using a Principal Component Analysis, all the cognitive measures were grouped in four high-order factors, reflecting (a) General Cognitive Abilities, (b) Speed of Linguistic Elaboration, (c) Accuracy in Reading and Memory tests and (d) Visuospatial and numerical skills. The longitudinal comparison of the four groups of students revealed that students from the Music curriculum had better performance in tests tackling General Cognitive Abilities, Visuospatial skills, and Accuracy in Reading and Memory tests. However, there were no significant curriculum-by-time interactions. Finally, the decision to have a musical experience before entering middle school was more likely to occur when the cultural background of the families was a high one. We conclude that a combination of family-related variables, early music experience, and pre-existent cognitive make-up is a likely explanation for the decision to enter a music curriculum at middle school.